PREVALENCE AND CLINICAL CORRELATES OF FRAILTY IN HYPERTENSIVE OLDER ADULTS. (June 2022) - Rivasi, Giulia; Tortu, Virginia; D'Andria, Maria Flora; Turrin, Giada; Ceolin, Ludovica; Capacci, Marco; Mossello, Enrico; Ungar, Andrea
Abstract : Objective: To assess the prevalence of frailty among hypertensive older adults according to the most widely used frailty measure tools and to investigate the clinical correlates of frailty. Design and method: A prospective observational study was conducted involving consecutive hypertensive patients aged 75 or older referred to a Hypertension clinic or a Memory clinic in Florence, Italy. The following frailty measure tools were applied: Fried Frailty Phenotype (FFP), Frailty Index, Clinical Frailty Scale (CFS), Frailty Postal Score (FPS), Short Physical Performance Battery (SPPB), gait velocity. The Cohen's kappa coefficient was calculated to assess the agreement among measures. Multiple logistic regression was used to identify clinical variables independently associated with frailty ("correlates of frailty''). Results: The study sample included 121 participants (mean age 81, 60% female). Frailty prevalence varied according to the definition used, ranging from 33% according to the FPS up to 50% according to the CFS. The Cohen's kappa coefficient indicated moderate agreement of the FFP with the Frailty Index and the SPPB, and of the Frailty Index with the CFS and the SPPB (K = 0.60–0.79). Agreement was minimal or weak among the remaining measures (K < 0.60). At multivariable analysis, using a walking aid and reporting depressive symptoms at the Geriatric Depression Scale were independently associated with frailty, regardless of the frailty measure used. Correlates of frailty also included dementia, disability in instrumental activities of daily living (Frailty Index, CFS, gait velocity) and the comorbidity burden (Frailty Index, gait velocity). Regular physical activity was inversely associated with frailty when defined according to the FFP, the Frailty Index and the FPS. Conclusions: Frailty is common among older adults with hypertension, although prevalence varies depending on the definition used. Agreement among different frailty measures was moderate-to-weak. Multiple correlates of frailty were identified, including factors that are not routinely assessed in hypertensive patients, such as depressive symptoms and disability. Depressive symptoms and walking aids could represent frailty markers in hypertensive older adults, irrespective of how frailty is defined.